Stanhopeinae Mesoamericanae VI. On the identity of Polycycnis barbata (Orchidaceae), and other notes on the genus Polycycnis - Gerlach, Günter; Pupulin, Franco (Phytotaxa, 2020)
The identity of Polycycnis barbata is discussed and, upon examination of the type, the name is lectotypified and synonymized under the species with erect, small-flowered inflorescence traditionally known as P. muscifera. The large-flowered species of Polycycnis from Costa Rica and northwestern Panama is described as P. grandiflora and illustrated based on Costa Rican material. Notes on distribution, chemistry and pollination of the new species and an overview of the genus Polycycnis are provided.